2002
DOI: 10.1016/s0375-9474(02)00777-7
|View full text |Cite
|
Sign up to set email alerts
|

R-process nucleosynthesis in core-collapse supernova explosion

Abstract: We study the r-process nucleosynthesis in neutrino-driven winds of gravitational core collapse SNeII. Appropriate physical conditions are found for successful r-process nucleosynthesis, which meet with several features of heavy elements discovered recently in metal-deficient halo stars. We find also several difficulties which are not explained in the present wind models. We discuss quests for new insights in nuclear physics, astrophysics, and astronomy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…This may lead to a slightly smaller neutron-to-seed ratio at the onset of r-process, and hence make an appreciable influence on the entropy condition and expansion dynamics of the neutrino-driven wind [4]. Kajino et al have recently studied the sensitivity of the r-process yields to the α(αn, γ) 9 Be reaction rate, and found that a factor of two larger rate would change the final r-process abundances drastically in rapid expansion models of the neutrino-driven wind [45]. These possible implications should be studied in detail by using the present new reaction rate.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This may lead to a slightly smaller neutron-to-seed ratio at the onset of r-process, and hence make an appreciable influence on the entropy condition and expansion dynamics of the neutrino-driven wind [4]. Kajino et al have recently studied the sensitivity of the r-process yields to the α(αn, γ) 9 Be reaction rate, and found that a factor of two larger rate would change the final r-process abundances drastically in rapid expansion models of the neutrino-driven wind [45]. These possible implications should be studied in detail by using the present new reaction rate.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The reaction rate for 8 Li(α,n) 11 B is taken from Gu et al (1995). This reaction was identified to be a critical nuclear reaction of producing the intermediate-to-heavy mass elements in some inhomogeneous Big-Bang nucleosynthesis models (Malaney & Fowler 1988, Boyd & Kajino 1989, Kajino & Boyd 1990 as well as for r-process nucleosynthesis (Terasawa et al 2001, Kajino, Wanajo & Mathews 2002. Ishiyama et al (2004) have recently carried out very precise measurements of the exclusive reaction cross section for 8 Li(α, n) 11 B * as well as for 8 Li(α, n) 11 B gs .…”
Section: Li(nγ) 8 LImentioning
confidence: 99%
“…These nuclei are important for analysis of the r-process in stars [35][36][37]. As in the previous Sec.…”
Section: Two-neutron Drip Linementioning
confidence: 78%
“…This part of the nuclear chart is important for the study of the r-process in stars [35][36][37]. The consideration is made within a standard approach with fixed EDF parameters found mainly for stable nuclei.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation